Managing Forests and Water for People under a Changing Environment - Sun, Ge (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Forests cover 30% of the Earth's land area, or nearly four billion hectares. Enhancing the benefits and ecosystem services of forests has been increasingly recognized as an essential part of nature-based solutions for solving many emerging global environmental problems today. A core science supporting forest management is understanding the interactions of forests, water, and people. These interactions have become increasingly complex under climate change and its associated impacts, such as the increases in the intensity and frequency of drought and floods, increasing population and deforestation, and a rise in global demands for multiple ecosystem services including clean water supply and carbon sequestration. Forest watershed managers have recognized that water management is an essential component of forest management. Global environmental change is posing more challenges for managing forests and water toward sustainable development. New science on forest and water is critically needed across the globe. The International Forests and Water Conference 2018, Valdivia, Chile (http://forestsandwater2018.cl/), a joint effort of the 5th IUFRO International Conference on Forests and Water in a Changing Environment and the Second Latin American Conference on Forests and Water provided a unique forum to examine forest and water issues in Latin America under a global context. This book represents a collection of some of the peer-reviewed papers presented at the conference that were published in a Special Issue of Forests.